2018
DOI: 10.1136/bmjopen-2017-019237
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions, experiences and expectations of physicians regarding the role of pharmacists in low-income and middle-income countries: the case of Tehran hospital settings

Abstract: ObjectivePharmacists play a pivotal role in the health continuum, and the perceptions and expectations of physicians towards pharmacists have been reported as a key factor in the interprofessional relationship. This study aimed to elicit the perceptions and expectations of physicians towards the role of pharmacists in hospitals to clarify the level of interaction between physicians and pharmacists in hospital settings.DesignA cross-sectional survey using a self-administered questionnaire was conducted to colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 38 publications
(30 reference statements)
4
39
0
Order By: Relevance
“…However, physicians consider pharmacists as knowledgeable drug-therapy experts, and they are positively receptive to several clinical services provided by the pharmacist with some reservations. [2][3][4][5][6][7] Studies have proved that a better collaboration between healthcare providers and pharmacists has led to safer, more effective and less costly drug therapies. [8][9][10] In 2011, a study conducted by Zidane et al 10 in our institute, which aimed to investigate the physicians' perceptions and expectations from their experiences with the pharmacists at Hamad Medical Corporation (HMC), the largest governmental healthcare organization in Qatar, found that physicians were comfortable working with pharmacists and had high expectations of pharmacists in performing their duties.…”
Section: Introductionmentioning
confidence: 99%
“…However, physicians consider pharmacists as knowledgeable drug-therapy experts, and they are positively receptive to several clinical services provided by the pharmacist with some reservations. [2][3][4][5][6][7] Studies have proved that a better collaboration between healthcare providers and pharmacists has led to safer, more effective and less costly drug therapies. [8][9][10] In 2011, a study conducted by Zidane et al 10 in our institute, which aimed to investigate the physicians' perceptions and expectations from their experiences with the pharmacists at Hamad Medical Corporation (HMC), the largest governmental healthcare organization in Qatar, found that physicians were comfortable working with pharmacists and had high expectations of pharmacists in performing their duties.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, cooperation between physicians and pharmacists is necessary for the safe and effective use of medications in hospitals. 17,18 Moreover, in the present study the dosing of antibiotics based on renal function was incorrect in nearly 35% of cases. The significant impact of pharmacists on appropriate renal dosing adjustment of antibiotics in an ED has been reported previously.…”
Section: Discussionmentioning
confidence: 57%
“…In addition, prescribing medications is a collaborative process that includes the skills and experience of both physicians and pharmacists. Accordingly, cooperation between physicians and pharmacists is necessary for the safe and effective use of medications in hospitals . Moreover, in the present study the dosing of antibiotics based on renal function was incorrect in nearly 35% of cases.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations